Investigation of the factors that impact on e-government readiness in Limpopo Province, South Africa : a case of the Department of Transport and Community and Safety - Boshielo, Shela Polly (My University, 2025)
In South Africa, the development of Information and Communication Technologies (ICTs) infrastructure remains inadequate, both in government spheres and amongst private sector stakeholders. Despite the potential of digital technologies to enhance the lives of people in various sectors of the economy, the South African government still faces several challenges in its efforts to improve the extent and quality of public service delivery to its people. This makes the ideal of using ICTs for development a not-yet-achieved goal. This study investigated the factors influencing eGovernment readiness in the Limpopo Province’s Department of Transport and Community Safety (DTCS). Data was collected using a semi-structured questionnaire, completed by selected officials at the DTCS who were knowledgeable about ICTs and the implementation of digital technologies for public service delivery. The second data source was from interviews, using an interview guide prepared for community members both from business and non-business backgrounds. The community stakeholder participants, as a group, included both those knowledgeable about the use of ICTs by governments and those who were not knowledgeable about it. The findings revealed that the implementation of ICTs, as a tool for achieving effective service delivery, is important, but that to be effective the right conditions are required. Historically disadvantaged communities, such as the rural population in Limpopo Province, still lag in their ability to find and use digital technologies to access the government’s public services platforms. Political, social, and economic factors influence this experience. A clear understanding by the government of the need for a coherent implementation strategy for ICTs (that considers all the limiting political, socio-economic, and cultural factors in the provision of mainstream public services) is crucial to ensuring success. Recommendations for future research are provided
Thesis (Ph.D. (Administration)) -- University of Limpopo, 2025
Keywords: Development of information and communication technologies; e-goverment; Information and Communication Technologies; Information storage and retrieval systems; Internet in public administration; Information technology